UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA (STUDI KASUS DI SMA NEGERI 1 KOTA BIMA) - Nasrullah Nasrullah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2018)
The purpose of the study was to find out the character values applied and the efforts of Islamic education teachers in shaping the character of students in the State 1 High School in Bima City. This study uses a qualitative, descriptive-analytic approach that analyzes data empirically. This type of research is a case study, while data and data sources in the form of words, behavior, and actions of Islamic religious education teachers. Data collection techniques are observation, interviews, and documentation. Data analysis is used by using an interactive model data analysis component. The conclusions are: First, the application of character values to students has been carried out by the school through intracuricular and extracurricular activities, namely: (1) integrating the values of character education in the subjects taught by the teachers; and (2) holding yasinan (al-Qur'an) together every Friday and scouting. Second, the efforts of Islamic religious education teachers in shaping student character, namely: (1) integrating Islamic religious education subjects with national character values; (2) Qur'anic literacy training, religious lectures (Islam) and familiarizing students with prayer in congregation; (3) applying good character in social and interactive relationships.